1974
DOI: 10.1002/1097-0142(197405)33:5<1423::aid-cncr2820330529>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The human pancreatic islet cells and their tumors.II. Ulcerogenic and diarrheogenic tumors

Abstract: A comparative histologic examination of hematoxylin‐eosin stained sections of 34 ulcerogenic tumors of the pancreas (UTP), 5 diarrheogenic tumors of die pancreas (DTP), 13 beta cell tumors, and 4 alpha cell tumors revealed two correlative features: all tumors characterized by a gyriform pattern of growth throughout the lesion were either of alpha or beta cell origin, and all but 1 of the tumors containing glandular formations were of either UTP or DTP type. No differential morphological features were found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1974
1974
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 61 publications
0
11
0
1
Order By: Relevance
“…Although multiple giant gastric ulcers which caused massive bleeding were found, gastrin production was ruled out immunohistologically (5). However, endocrine tumors of the pancreas may be ulcerogenic, and the possibility that the giant ulcers may have been caused by some unknown hormones produced by this neuroendocrine tumor cannot be ruled out completely (18,19). Genetic abnormalities which cause von Hippel-Lindau disease have becomeclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple giant gastric ulcers which caused massive bleeding were found, gastrin production was ruled out immunohistologically (5). However, endocrine tumors of the pancreas may be ulcerogenic, and the possibility that the giant ulcers may have been caused by some unknown hormones produced by this neuroendocrine tumor cannot be ruled out completely (18,19). Genetic abnormalities which cause von Hippel-Lindau disease have becomeclear.…”
Section: Discussionmentioning
confidence: 99%
“…Most cells stain with argyrophilic dyes or with antisera directed against pancreatic glucagon (4-6, 10, 20, 51, 67, 73, 76, 84, 94, 95). Secretory granules are usually found in at least some cells of a given neoplasm, appearing uniformly either as mature forms or as granules of varying electron density ranging between 100-400 nm in diameter (13,15,20,23,51,73,76,88,95,106). They may show an eccentrically placed core and contain a halo (51,73,106), or they may be homogenous (13,73,76,106).…”
Section: Summer 1981mentioning
confidence: 99%
“…These APUD or neuroendocrine cells scattered throughout the foregut are seen in gastric, duodenal, and bronchial carcinoid tumors. 20,21 Although there are many reports of melanin pigment identified in carcinoid tumors of the lung and thymus, among others, there have not been well-documented reports of pancreatic carcinoid tumors in which melanin has been identified absolutely. Pearse and Takor 19 concluded that the carcinoid tumor does not arise from the enterochro- maffin cell but from a multipotential precursor.…”
Section: Discussionmentioning
confidence: 99%